PENGEMBANGAN UMKM BERBASIS POTENSI DESA MELALUI INOVASI PRODUK DONAT WALUH (LABU KUNING) DI DESA RENGEL - Dzurotun Khanifah M; Fathimatuz Zahro; Nissa Ariyanti; Hafsah Al Faidah; NurKholifah; M. Ihya'uddin Salim; Alfianti Sumsurrohmah; Siti Sholikah; Alfi Manzilatir Rohmah; Putri, Denada; Ahmad Bahrudin (CV. Kalimasada Group, 2025)
This study aims to develop Micro, Small, and Medium Enterprises (MSMEs) in Rengel Village, Tuban Regency, through the innovation of pumpkin-based (waluh) donuts as a utilization of local potential. The research uses the Asset-Based Community-Driven Development (ABCD) approach, which emphasizes community empowerment through asset mapping, shared vision, action design, and sustainable implementation. The research stages include preparation of ingredients, dough mixing, shaping, fermentation, frying, cooling, topping, packaging, and product evaluation. The results show that the pumpkin donut innovation can improve community skills in food processing, add value to local ingredients, and create new business opportunities based on village resources. The pumpkin donuts have a soft texture, balanced sweetness, attractive appearance, and high nutritional content, thus potentially enhancing community welfare through local MSME development. This study provides both theoretical and practical contributions to the development of local resource-based product innovations.